Mutation screening of candidate genes and the development of polymorphic markers residing on chromosome 19q13.3, the progressive familial heart block I gene search area - Makubalo, Zola (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.